(untitled) (Global Journal of Medical Research, 2016)
Primary urethral carcinoma is a very rare urinary tract cancer with very few reported cases all over the world. Owing to limited trials and research work due to the rarity there is no standardization of the treatment protocol. We report a case of a 60 yrs female presenting with hematuria who underwent surgical resection of urethra and was diagnosed to be a case of Primary Urethral adenocarcinoma.